Pengaruh Penggunaan Brainly terhadap Pemahaman Belajar Siswa pada Jenjang SD/MI, SMP/MTs, dan SMA/SMK/MA (Insan Cendekia : Jurnal Pendidikan dan Kebudayaan, 2024)
Learning comprehension refers to students’ ability to understand and construct meaning from concepts rather than merely memorize information. The rapid development of technology has influenced education by providing students with easier access to learning resources and information. This study aims to examine the influence of Brainly on students’ learning comprehension. A quantitative approach with a survey method was employed, using questionnaires as the main instrument for data collection. The respondents consisted of 56 students from elementary, junior high, and senior high school or equivalent levels in Pamekasan, Bandung, Palembang, and Palu. The results showed that Brainly was widely used by students as a supporting platform for learning and completing school assignments. A total of 33 respondents (58.9%) reported being satisfied with their learning comprehension after using Brainly, while 23 respondents (41.1%) reported otherwise. The average score for the perceived benefits of Brainly was 5.6. In addition, 41 respondents stated that Brainly had a positive impact on learning, while 15 respondents perceived negative effects. These findings indicate that Brainly can support students’ learning comprehension and facilitate access to learning resources. However, its use needs to be accompanied by appropriate supervision because excessive dependence on the platform may reduce students’ motivation to learn independently, critical thinking, and confidence in their own abilities.